DETERMINAN KINERJA KEUANGAN PERUSAHAAN IDX30: PENGUJIAN PENGARUH PROFITABILITAS DAN SOLVABILITAS - Naza Nadila Putri; Wiwin Sukiati; Hetti Herawati; Wuri Handayani (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2026)
Financial performance is an important indicator used to evaluate a company's ability to manage its resources efficiently and create sustainable value. This study aims to examine the effects of profitability and solvency on the financial performance of IDX30 companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employed a quantitative approach using secondary data obtained from audited annual financial reports. The sample consisted of 17 companies selected through purposive sampling, and the data were analyzed using panel data regression. The findings indicate that profitability has a positive effect on financial performance, while solvency has a negative effect on financial performance. These results suggest that improving profitability and maintaining an optimal capital structure are essential to enhancing corporate financial performance. The study contributes empirical evidence on the determinants of financial performance among large-cap companies in the Indonesian capital market.